RANCANG BANGUN SISTEM ALAT PRAKTIKUM SCR DI LABORATORIUM ELEKTRONIKA DAYA DENGAN PENGENDALI ARDUINO - Fendi Rahmad; Sunu Pradana; Abdul Hamid Kurniawan (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2021)
Silicon Controlled Rectifier (SCR) is one of the components studied in the Power Electronics course at the Department of Electrical Engineering, Samarinda State Polytechnic. Therefore, in the SCR learning process, a practicum module is needed as a learning support tool. The practicum modules in the Power Electronics laboratory are prone to damage and are difficult to repair, so updating tools with simpler maintenance and operation needs to be done. In the module that has been designed, the operation of the SCR is carried out by detecting the zero crossing point on the sinusoidal waveform of the source voltage. Detection is carried out by the zero cross detector module which then sends pulses to the Arduino Mega. The pulse will be used by Arduino Mega to send a trigger pulse signal to the SCR gate leg. The delay time of the trigger pulse is set by the program in the Arduino to get the desired triggering angle. In the test, the SCR module was operated as a single-phase half-wave controlled rectifier, a single-phase full-wave controlled rectifier with a center-tap transformer, a bridge system single-phase full- wave controlled rectifier, and a three-phase half-wave controlled rectifier. As a result, the triggering angle is inversely proportional to the value of the output voltage and current parameters. As the value of the trigger angle is increased, the value of the output voltage and current of the controlled rectifier will decrease.